A New Hydroxychavicol Dimer from the Roots of Piper betle - Huei-Yu Tu; Horng-Liang Lay; Chun-Chien Chien; Chwan-Fwu Lin; Tsong-Long Hwang (Molecules, 2013)
A new hydroxychavicol dimer, 2-(g'-hydroxychavicol)-hydroxychavicol (1), was isolated from the roots of Piper betle Linn. along with five known compounds, hydroxychavicol (2), aristololactam A II (3), aristololactam B II (4), piperolactam A (5) and cepharadione A (6). The structures of these isolated compounds were elucidated by spectroscopic methods. Compounds 1 and 2 exhibited inhibitory effects on the generation of superoxide anion and the release of elastase by human neutrophils.